Sustainable agriculture: where are we on SDGs implementation? Reader for Brussels Briefing 54 - Boto, Isolina; Mofolo, Lebo (Technical Centre for Agricultural and Rural Cooperation, 2019)
In September 2015 Heads of State and Government agreed to set the world on a path towards sustainable development through the adoption of the 2030 Agenda for Sustainable Development. The information in this document was compiled as background reading material for the 54th Brussels Briefing on “Sustainable agriculture: where are we on SDGs implementation?”